АКТУАЛЬНІ АСПЕКТИ ФОРМУВАННЯ В УЧНІВ ЗДОРОВОГО СПОСОБУ ЖИТТЯ (Педагогіка вищої та середньої школи, 2022)
In the article look at actual aspects increase level of health for children and have owning habits and skill of health life.